Foreign language anxiety levels in Second Life oral interaction. Issue 1 (27th October 2016) - Melchor-Couto, Sabela
Abstract: Virtual worlds have been described as low anxiety environments (Dickey, 2005), where students may feel "shielded" behind their avatars (Rosell-Aguilar, 2005: 432). The aim of this article is to analyse the evolution of the Foreign Language Anxiety (FLA) levels experienced by a group of participants who used the virtual world Second Life for oral interaction (VW Group). The data gathered was compared to that of a group of students who completed similar oral interaction activities in the traditional classroom (CR Group). The quantitative and qualitative data analysed indicates that the FLA levels of the VW Group decreased as weeks went by and that they were lower than those experienced by the CR Group. The anonymity afforded by the VW had a positive effect on some of the students, who reported increased self-confidence and decreased nervousness. However, the students' comments suggest that this anonymity may wear off once they feel they know their interlocutor. Anonymity may not be the only reason to explain the decrease in FLA.